2019
DOI: 10.1002/joc.6452
|View full text |Cite
|
Sign up to set email alerts
|

A climatological study of the wet and dry conditions in the pre‐summer monsoon season of the Philippines

Abstract: This study investigates the climatology of the wet and dry conditions in the presummer monsoon season of the Philippines that are less emphasized in previous works. Wet cases (Type W), which account for about 23% of the total presummer monsoon days from 1979 to 2015, are identified from April 1 to the monsoon onset defined by the Philippine Atmospheric, Geophysical, and Astronomical Services Administration (PAGASA). The differences between the Type W and dry cases (Type D) are presented. The synoptic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Before the monsoon break period, rainfall in all the stations increases to as much as 38 mm⋅day −1 , except for Laoag station, where the rainfall first peaks at Lag −14 and exceeds 50 mm⋅day −1 . This location frequently experiences heavy rainfall events associated with shearlines (Olaguera and Matsumoto, 2020). During the monsoon break period, the rainfall drops below 5 mm⋅day −1 in all the stations and increases again to about 10 mm⋅day −1 after Lag +6.…”
Section: Resultsmentioning
confidence: 99%
“…Before the monsoon break period, rainfall in all the stations increases to as much as 38 mm⋅day −1 , except for Laoag station, where the rainfall first peaks at Lag −14 and exceeds 50 mm⋅day −1 . This location frequently experiences heavy rainfall events associated with shearlines (Olaguera and Matsumoto, 2020). During the monsoon break period, the rainfall drops below 5 mm⋅day −1 in all the stations and increases again to about 10 mm⋅day −1 after Lag +6.…”
Section: Resultsmentioning
confidence: 99%
“…The lower boundary of the negative meridional gradient of equivalent potential temperature ( e925hPa y ) can be used to locate the mean position of the cold front (e.g., Olaguera and Matsumoto 2020;Olaguera et al 2021), as shown in Fig. 2a, c, e, and g and superimposed with the winds at 925 hPa (WINDS 925hPa ).…”
Section: Synoptic Conditions During the January 2009 Hrfmentioning
confidence: 99%
“…They further noted that the presence of a westward propagating low-pressure area over Mindanao Island further enhanced the interaction between the warm easterlies over the tropical region and cold northeasterlies. The impact of cold surge shearlines is also observed during pre-summer (e.g., Olaguera and Matsumoto 2020) where it contributes to the pre-summer monsoon rainfall of the northern Philippines. Based on these aforementioned studies, it is recognized that the cold surge shearline is another synoptic-scale system that induces HRF events over the country especially during the northeast monsoon season.…”
Section: Introductionmentioning
confidence: 99%
“…More quantitative analysis are needed to firmly present the effect of TCs on the rainfall over the Philippines. Moreover, in addition to TCs, some other synoptic systems, such as midlatitude front or disturbances (e.g., Olaguera and Matsumoto, 2019;Olaguera et al, 2020a), or local rain systems such as diurnally driven local circulation are also contributing to the rainfall. The contribution from these systems on climatological rainfall seasonal changes should also be studied in future.…”
Section: Discussionmentioning
confidence: 99%
“…The wind over the Philippines tends to have more southerly component in this season. This indicates that the confluence zone between the westerly and easterly shifts eastward in the east of the Philippines due to the eastward retreat of the WNPSH (Olaguera et al, 2018a(Olaguera et al, , 2018b(Olaguera et al, , 2020b. The monsoon trough is located in the central part of the Philippines.…”
Section: Climatological Features Of Rainfall and Low Level Circulationmentioning
confidence: 93%